MOFs-loaded polymer composite material as well as preparation method and application thereof

Through the frozen crushing and melt blending process, MOFs nanoparticles are loaded to the surface of polymer materials, solving the problems of low utilization rate of MOFs nanomaterials and difficult to control the particle size in the prior art, and achieving efficient and economical preparation of water treatment materials.

CN119591930APending Publication Date: 2025-03-11BEIJING UNIV OF CIVIL ENG & ARCHITECTURE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411365853.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When loading MOFs nanoparticles into thermoplastic polymer plastics, the problems of high equipment accuracy requirements, continuous porous structure of the polymer internal structure, resulting in low utilization of MOFs nanomaterials and difficult to control the particle size.

Method used

The freeze-breaking and melt-blending process is adopted to freeze-break the polymer material and then add MOFs material for melt-blending, so that the MOFs material is loaded on the surface of the polymer material. The particle size is accurately controlled by controlling the grinding speed and time, and the heating and stirring conditions in the coffee roaster are used to form a graded porous polymer millinan structural composite material with MOFs loading.

Benefits of technology

The rapid and simple preparation of polymer composites loaded with MOFs is achieved, which improves production efficiency, reduces costs, enhances the utilization rate of MOFs, the operability of composite materials and compatibility with actual water treatment devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental engineering, and particularly relates to an MOFs-loaded polymer composite material as well as a preparation method and application thereof. The preparation method of the MOFs-loaded polymer composite material comprises the following steps: freezing and crushing a polymer material, then adding an MOFs material, carrying out melt blending, enabling the MOFs material to be loaded on the surface of the polymer material, cooling, and separating to obtain the MOFs-loaded polymer material. The graded porous MOFs-loaded polymer composite material is rapidly and simply prepared in batches by taking waste plastic in household garbage as a raw material, combining a freezing crushing process and a melt blending process and utilizing the difference of surface and interface properties generated by different temperature differences and different materials and the rule of oxygen concentration distribution; the potential of the MOFs for realizing large-scale water treatment application is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental engineering technology, specifically relating to a polymer composite material supported on MOFs, its preparation method, and its application. Background Technology

[0002] Traditional methods of recycling waste plastics involve crushing them and then melting them down to reshape them into new plastic products. However, due to the aging process of plastics over time, the mechanical strength and durability of the products produced by this method are lower than those of the original products, resulting in a low utilization rate of waste plastics. Therefore, the effective recycling and reuse of waste plastics has become an urgent task.

[0003] Metal-organic frameworks (MOFs) are an emerging type of functional material ranging from micrometers to nanometers. Their unique tunable structure, ultra-large specific surface area, and abundant active sites make them widely applicable in adsorption, catalysis, sensing, antibacterial applications, drug delivery, and energy. Particularly in water pollution removal, MOFs possess a large specific surface area and strong interfacial effects, enabling them to efficiently adsorb organic pollutants and inorganic ions in water. They can also degrade and transform various toxic and harmful substances in water by photocatalysis or activation of other oxidants to generate a variety of reactive species. However, the problems of MOF nanomaterials, such as easy aggregation and deactivation, difficulty in separation, poor stability, and potential environmental risks, cannot be underestimated and represent one of the main bottlenecks in their current engineering applications.

[0004] Fortunately, loading MOF nanoparticles onto millimeter-sized waste plastic microparticles combines the high reactivity of nanoparticles with the excellent operability of millimeter-sized carriers, leveraging their respective strengths and overcoming their limitations. This not only promotes the practical application of MOF nanomaterials but also implements the "3R" principle (Reduce, Reuse, Recycle) for waste management, saving raw materials needed for producing water treatment functional materials and reducing waste accumulation in the environment, thus making a significant contribution to sustainable development. However, the commonly used method for loading MOFs into thermoplastic polymers in industrial production is still the hot melt extrusion method. This involves mixing MOF powder with thermoplastic polymer particles in an extruder, heating it to the polymer's melting temperature, and then extruding it again to form a mixed material with a certain particle size. This method is difficult to extrude into millimeter-sized particles and requires highly precise equipment. In addition, most polymers have a continuous, non-porous internal structure, preventing the MOF powder doped inside from contacting the external environment, thus reducing the utilization rate of MOF nanomaterials. Therefore, it is of great significance to develop a technical solution that effectively utilizes waste plastics and loads MOF nanoparticles onto the surface of millimeter-scale plastic microparticles. Summary of the Invention

[0005] The technical problem solved by this invention is: pollution from waste plastics, and the problems that MOF nanoparticles have during application, such as easy agglomeration, difficulty in recycling, easy loss, poor stability and easy clogging of reactors. The existing MOFs-polymer composite material preparation process has problems such as large consumption of polymer raw materials, high overall cost of preparation process, low utilization rate of MOFs nanomaterials and difficulty in controlling particle size.

[0006] To address the aforementioned technical problems, this invention provides a polymer composite material supported on MOFs, its preparation method, and its application.

[0007] Specifically, the present invention provides the following technical solution:

[0008] In a first aspect, the present invention provides a method for preparing a polymer composite material loaded with MOFs, comprising the following steps: freezing and crushing a polymer material, then adding MOFs material for melt blending, so that the MOFs material is loaded on the surface of the polymer material, cooling, separating, and obtaining a polymer material loaded with MOFs.

[0009] Preferably, the polymer material is a material containing a thermoplastic polymer.

[0010] Preferably, the polymer material is a plastic product containing a thermoplastic polymer.

[0011] More preferably, the thermoplastic polymer includes one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyethylene terephthalate, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, and acrylonitrile-butadiene-styrene trimer.

[0012] More preferably, the thermoplastic polymer includes one or more of polyethylene, polypropylene, polystyrene, and polyethylene terephthalate.

[0013] Preferably, the MOFs material is a MOFs material with a thermal decomposition temperature higher than 120°C.

[0014] Preferably, the MOFs material is selected from ZIF-8, ZIF-67, ZIF-L, ZIF-9, ZIF-90, PCN-222, PCN-224, IRMOF-3, IRMOF-8, IRMOF-9, HKUST-1, Cu-TCPP, MOF-5, MOF-74, MOF-808, MOF-525, MIL-53 (Cr / Al / Fe), MIL-100 (Fe / Cr), MIL-101 (Fe / Cr), and MIL-125 (Ti). One or more of the following: MIL-88A(Fe), MIL-88B(Fe), MIL-68(Al / Fe), NH2-MIL-125(Ti), NH2-MIL-88B(Fe), NH2-MIL-53(Al), UiO-66(Zr), NH2-UiO-66(Zr), UiO-66(Zr)-(OH)2, UiO-66(Zr)-COOH, UiO-66(Zr)-SO3H, UiO-67(Zr) and UiO-68.

[0015] More preferably, the MOFs material is selected from one or more of ZIF-8, ZIF-67, ZIF-L, ZIF-9, ZIF-90, MIL-53 (Cr / Al / Fe), MIL-100 (Fe / Cr), MIL-101 (Fe / Cr), MIL-125 (Ti), MIL-88A (Fe), MIL-88B (Fe), MIL-68 (Al / Fe), NH2-MIL-125 (Ti), NH2-MIL-88B (Fe), NH2-MIL-53 (Al), and UiO-66 (Zr).

[0016] Preferably, the freezing conditions are: the freezing temperature is -20 to -80°C.

[0017] Preferably, the freezing temperature is -60 to -70°C.

[0018] Preferably, the freezing time is 1 to 30 seconds.

[0019] More preferably, the freezing time is 5 to 7 seconds.

[0020] Preferably, the crushing is performed using mechanical grinding.

[0021] Preferably, the conditions for mechanical grinding and crushing are: a grinding speed of 10,000 to 30,000 rpm.

[0022] Preferably, the grinding speed is 12000-13000 rpm.

[0023] Preferably, the grinding time is 1 to 30 seconds.

[0024] More preferably, the grinding time is 5 to 7 seconds.

[0025] Preferably, the particle size range of the polymer material after cryogenic grinding is 0.1 to 2.0 mm.

[0026] More preferably, the particle size range of the polymer material after crushing and grinding is 0.5 to 1.0 mm.

[0027] Preferably, MOFs are added to the cryogenically ground polymer material and mixed, followed by melt blending.

[0028] Preferably, the mass ratio of the MOFs to the cryogenically ground polymer material is 1:2 to 10.

[0029] More preferably, the mass ratio of the MOFs to the cryo-milled polymer material is 1:3 to 5.

[0030] Preferably, the hot-melt treatment is performed by heating and stirring, with the following conditions: heating temperature of 100-250°C; more preferably, heating temperature of 150-230°C; and / or, heating and stirring time of 1-10 min.

[0031] More preferably, the heating and stirring time is 2 to 4 minutes; and / or the stirring speed is 20 to 100 rpm; more preferably, the stirring speed is 60 to 80 rpm.

[0032] Preferably, the cooling is performed using a cooling molding agent.

[0033] Preferably, the mass ratio of the cooling molding agent to the polymer composite material loaded with MOFs is 10 to 50:1.

[0034] More preferably, the mass ratio of the cooling molding agent to the polymer composite material loaded with MOFs is 20 to 30:1.

[0035] Preferably, the cooling process takes 1 to 10 minutes.

[0036] More preferably, the cooling process takes 4 to 7 minutes.

[0037] Preferably, the cooling molding agent is selected from one or more of water, ethanol, and N,N-dimethylformamide.

[0038] More preferably, the cooling molding agent is water.

[0039] Preferably, a polymer composite material supported on MOFs is provided, wherein the polymer composite material supported on MOFs is prepared by the preparation method described above.

[0040] Secondly, the present invention provides an application of the aforementioned MOF-loaded polymer composite material in the field of adsorption removal of pollutants in water or oxidative degradation of pollutants in water.

[0041] Preferably, the application of the polymer composite material loaded with MOFs in the adsorption and removal of arsenic pollutants in water.

[0042] Preferably, the application of the MOF-loaded polymer composite material in the field of oxidative degradation of organic pollutants in water.

[0043] Preferably, the organic pollutant is an antibiotic.

[0044] Preferably, the oxidative degradation of antibiotic contaminants in water includes one or more of the following: degradation of water contaminants based on activated hydrogen peroxide, degradation of water contaminants based on activated persulfate, and degradation of water contaminants based on activated ozone.

[0045] Thirdly, the present invention provides an application of the aforementioned MOF-loaded polymer composite material in the preparation of flame-retardant products.

[0046] Fourthly, the present invention provides a continuous operation device for removing pollutants from water, characterized in that the device comprises: a liquid inlet system, a reaction system, and a liquid discharge system;

[0047] The liquid inlet system is used to introduce the wastewater to be treated into the reaction system;

[0048] The reaction system is loaded with a polymer composite material containing MOFs to remove pollutants from the wastewater to be treated.

[0049] The liquid discharge system is used to discharge the water treated in the reaction system.

[0050] Preferably, the liquid inlet system includes a storage tank 1 for storing wastewater to be treated, which is connected to the reaction system via a pipeline 3, and a centrifugal pump 2 is provided on the pipeline 3.

[0051] Preferably, the pipeline 3 is equipped with a first flow control valve 4.

[0052] Preferably, a first flow meter 5 is provided on the pipe 3.

[0053] Preferably, a pressure gauge 6 is provided on the pipe 3.

[0054] Preferably, the liquid inlet system further includes an oxidant storage tank 7 for introducing the oxidant into the reaction system, which is connected to the reaction vessel 14 via a second pipeline 10; a peristaltic pump 8 is provided on the second pipeline 10.

[0055] Preferably, the second flow control valve 9 is provided on the second pipe 10.

[0056] Preferably, a second flow meter 11 is provided on the second pipe 10.

[0057] Preferably, the oxidant storage tank 7 is used to store aqueous solutions of hydrogen peroxide, potassium persulfate, or sodium persulfate.

[0058] Preferably, the reaction system includes a reaction vessel 14 for directly filling a polymer composite material loaded with MOFs. The bottom of the reaction vessel is provided with an aeration disc 12, and the top and bottom of the reaction vessel are respectively provided with a first flange 13 and a second flange 15 for sealing the reaction vessel. The first flange 13 is located below the aeration disc 12.

[0059] Preferably, the first flange 13 and the second flange 15 are respectively provided with a barrier mesh, the aperture of which is preferably 30 to 60 mesh, to prevent the loss of polymer composite material loaded with MOFs while ensuring normal water flow.

[0060] Preferably, the continuous operation device further includes an ozone generator 16 for supplying ozone to the reaction vessel 14, which is connected to the bottom of the reactor 14 via a pipe 19; a third flow control valve 17 is provided on the pipe 19.

[0061] Preferably, a third flow meter 18 is provided on the pipe 19.

[0062] Preferably, the liquid discharge system includes an outlet water collection tank 23, which is connected to the top of the reaction vessel 14 via a pipe 20; a fourth flow control valve 21 is provided on the pipe 20; and / or, a fourth flow meter 22 is provided on the pipe 20.

[0063] Beneficial effects of the present invention

[0064] (1) This invention uses waste plastics from municipal solid waste as raw materials, and combines freeze crushing and melt blending processes. By taking advantage of the differences in surface and interface properties caused by different temperature differences and different materials, as well as the law of oxygen concentration distribution, a polymer composite material with hierarchical porous MOFs is prepared quickly, simply and in batches.

[0065] (2) In the preparation method of the polymer composite material loaded with MOFs described in this invention, no additional reagents or surface modification processes are required, which significantly improves production efficiency, eliminates the need for long-term manual supervision and operation, and reduces the cost of preparing MOFs water treatment materials.

[0066] (3) The method for preparing the polymer composite material loaded with MOFs described in this invention solves the problem of recycling waste plastic resources and simultaneously reduces the amount of domestic waste, embodying the "3R" concept.

[0067] (4) The polymer substrate material supporting MOFs used in this invention is an existing material with low purchase cost, further enhancing the potential of MOFs for large-scale water treatment applications. Compared with micron-sized powders and centimeter-sized large particles, the nanostructured composite material (waste plastic microparticles after freeze-crushing are millimeter-sized polymer particles, while MOFs are micro-nano-sized particles, thus the combination of the two forms a nanostructured composite material) perfectly balances the contradiction between large specific surface area and separability. It not only retains the reactivity of MOF nanopowder materials, but also improves the operability of water treatment materials and their compatibility with actual water treatment devices, and is expected to become a bridge to promote MOFs water treatment functional materials from the laboratory to practical engineering applications. Attached Figure Description

[0068] Figure 1 Images of the MOFs materials prepared according to this invention are shown. In Figure (a), MIL-88A (Fe) is shown; in Figure (b), ZIF-67 is shown; and in Figure (c), UiO-66 (Zr) is shown.

[0069] Figure 2 These are scanning electron microscope (SEM) images of the MOF powders prepared in this invention. Figure (a) shows MIL-88A (Fe), Figure (b) shows ZIF-67, and Figure (c) shows UiO-66 (Zr).

[0070] Figure 3 The images show powder X-ray diffraction (PXRD) patterns of the MOF powders prepared in this invention. Figure (a) represents MIL-88A(Fe), Figure (b) represents ZIF-67, and Figure (c) represents UiO-66.

[0071] Figure 4 This is a photograph of the millimeter-sized PE particles used in this invention.

[0072] Figure 5 This is a SEM image of the surface of the millimeter-sized PE particles used in this invention.

[0073] Figure 6 These are photographs of the polymer nanostructured composite materials loaded with MOFs in this invention. Figure (a) shows the PE nanostructured composite material loaded with MIL-88A (Fe), Figure (b) shows the PE nanostructured composite material loaded with ZIF-67, and Figure (c) shows the PE nanostructured composite material loaded with UiO-66 (Zr).

[0074] Figure 7 These are SEM images of the surface of the polymer nanostructured composite material loaded with MOFs in this invention. Among them, Figure (a) shows the PE nanostructured composite material loaded with MIL-88A (Fe), Figure (b) shows the PE nanostructured composite material loaded with ZIF-67, and Figure (c) shows the PE nanostructured composite material loaded with UiO-66 (Zr).

[0075] Figure 8 This is a schematic diagram of the continuous operation device of Application Example 1 of the present invention.

[0076] Figure 9 This is a schematic diagram of the continuous operation device (including the main equipment dimensions) of Application Example 1 of the present invention.

[0077] Where 2 represents the diameter of the storage tank 1 and the water collection tank 23, 4 represents the height of the storage tank 1 and the water collection tank 23, 0.2 represents the diameter of the reaction vessel 14, and 3 represents the effective height of the packing material in the reaction vessel 14.

[0078] Figure 10 This is a schematic diagram of the continuous operation device in Application Example 2 of the present invention.

[0079] Figure 11 This is a schematic diagram of the continuous operation device (including the main equipment dimensions) of Application Example 2 of the present invention. Wherein, 2 represents the diameter of the liquid storage tank 1 and the effluent collection tank 23, and also the height of the oxidant storage tank 7; 1.2 represents the diameter of the oxidant storage tank 7; 4 represents the height of the liquid storage tank 1 and the effluent collection tank 23; 0.2 represents the diameter of the reaction vessel 14; and 3 represents the effective height of the packing material in the reaction vessel 14.

[0080] Figure 12 The adsorption and removal performance of total arsenic in groundwater and the detected dissolution of Fe ions were obtained after the reaction vessel of the continuously operating device in Application Example 1 of the present invention was filled with PE nanostructured composite material loaded with MIL-88A (Fe).

[0081] Figure 13 The degradation performance, TOC removal efficiency, and detected Fe ion dissolution of a mixture of tetracycline (TTC), oxytetracycline (OTC), and chlortetracycline (CTC) in water during the activation of H2O2 were measured in the reaction vessel of the continuously operating device in Application Example 2 of this invention after it was filled with PE nanostructured composite material loaded with MIL-88A (Fe).

[0082] Figure 14 Comparison of thermogravimetric curves of PE nanostructured composite materials loaded with MIL-88A (Fe), ZIF-67 and UiO-66 (Zr) in air atmosphere.

[0083] Figure 15This invention compares the limiting oxygen index during the combustion process of PE nanostructured composite materials loaded with MIL-88A (Fe), ZIF-67, and UiO-66 (Zr).

[0084] Among them, 1-storage tank, 2-centrifugal pump, 3-pipeline one, 4-first flow control valve, 5-first flow meter, 6-pressure gauge, 7-oxidant storage tank, 8-peristaltic pump, 9-second flow control valve, 10-pipeline two, 11-second flow meter, 12-aeration disc, 13-first flange, 14-reaction vessel, 15-second flange, 16-ozone generator, 17-third flow control valve, 18-third flow meter, 19-pipeline three, 20-pipeline four, 21-fourth flow control valve, 22-fourth flow meter, 23-effect water collection tank. Detailed Implementation

[0085] As described above, the purpose of this invention is to provide a polymer composite material supported on MOFs, its preparation method, and its application.

[0086] Crushing waste plastics into millimeter-sized particles and transforming them into excellent carriers for other functional materials is an effective way to recycle waste plastics. However, when using traditional crushers, the large amount of heat generated by the high-speed rotation of the shaft and blades can cause thermoplastics to melt, causing the already broken particles to re-adhere and agglomerate. Furthermore, the high-viscosity molten plastic can even clog and damage the crusher shaft and blades, rendering the entire equipment unusable. Therefore, there is an urgent need to find an improved crushing technology for processing waste plastics. Through dedicated research, the inventors of this application have discovered that using cryogenic crushing technology to crush waste plastics at low temperatures prevents the plastic from melting due to excessively high temperatures and maintains its rigidity, making it more conducive to being cut into finer particles by the blades. Specifically, cryogenic crushing technology refers to using the principle of refrigerant vaporization and heat absorption to rapidly reduce the internal temperature of the crusher chamber and perform grinding.

[0087] This invention ingeniously utilizes the differences in surface and interface properties caused by temperature differences, as well as the differences in surface and interface properties between two different materials at the same temperature (during melt blending, the MOF material interface remains rigid, while the polymer interface is flexible). It also leverages the localized temperature differences within a cryogenic crusher and the distribution of oxygen concentration at different stages of heating in a coffee roaster (the oxygen concentration at the polymer interface is lower than that further away from the polymer interface) to prepare a polymer nanostructured composite material with hierarchical porosity and loaded MOFs. The specific principle is as follows:

[0088] During the cryogenic crushing process, the particle size of the resulting millimeter-sized polymer particles can be precisely controlled by adjusting the grinding speed and grinding time (grinding and freezing occur simultaneously, with the grinding time being the freezing time). During grinding, the blades not only cut large materials into millimeter-sized particles but also create numerous incomplete micro-cuts on these particles. Subsequently, the cuts on the particles ejected from the blades are instantly cooled by the low temperature within the cryogenic crusher chamber, causing them to shrink and creating pits and channels. Ultimately, these particles, through countless repeated cutting and cooling processes, generate a large number of macroporous structures.

[0089] During the closed heating process of a coffee roaster, lattice water molecules and bound water molecules in MOFs (Metal-Oxide-Foil) molecules are heated, detach from the MOF molecules, and evaporate, generating a large amount of water vapor inside the roaster cavity. This water vapor condenses rapidly on the roaster lid and drips down the edge into the mixture of MOFs and millimeter-sized polymer particles. This condensate is reheated and turns back into water vapor. The resulting steam circulation creates an oxygen-deficient environment inside the roaster cavity, which helps carbonize the surface of the millimeter-sized polymer particles and form carbonaceous microdomains. The carbonaceous microdomains further reduce the oxygen concentration at the interface of the millimeter-sized polymer particles, and the carbon material itself can also effectively increase the ignition point of the resulting composite material, thereby jointly improving the flame retardant properties of the composite material and preventing combustion during the loading of MOF nanomaterials, which would cause material deactivation. At the same time, during continuous heating, the surface of the millimeter-sized polymer particles undergoes a transition from a glassy state and a highly elastic state to a viscous flow state. The viscosity between the interfaces of the molten polymer particles causes the particles to stick together, resulting in a larger particle size, which is not conducive to maintaining the millimeter-sized particle size. However, the incorporation of MOF nanoparticles can form a dense, layered structure between polymer surfaces, thus preventing particle adhesion and agglomeration. Furthermore, MOFs exhibit strong thermal stability, maintaining their rigidity even when the polymer transitions to a flexible, viscous flow state. Therefore, they can not only utilize the increased viscosity generated by molecular motion on the molten polymer surface, bonding to it through van der Waals forces and hydrogen bonds, but also form more pits and pores on the polymer particle surface through physical scraping and extrusion. This further facilitates the rapid entry of other MOF nanoparticles into these pits and pores, allowing them to adhere to the polymer surface. Ultimately, the micropores, mesopores, and macropores constructed by the millimeter-scale polymer surface of the MOF nanoparticles form a hierarchical (referring to the different pore sizes of micropores, mesopores, and macropores in the composite material formed by the MOF and polymer) porous polymer nanostructure composite material loaded with MOFs. Due to the physical isolation effect of the MOF powder, the polymer only undergoes surface melting, preventing the MOF powder from being embedded within the polymer.

[0090] In a first aspect, the present invention provides a method for preparing a polymer composite material supported on MOFs, comprising the following steps:

[0091] (1) Products containing polyethylene (PE), polypropylene (PP), polystyrene (PS), and / or polyethylene terephthalate (PET) from household waste collection stations were selected, cut into smaller pieces, and then further crushed using a cryogenic crusher. The cryogenic crusher temperature was set to -20 to -80℃, the grinding speed to 10,000 to 30,000 rpm, and the freezing / grinding time to 1 to 30 seconds, resulting in polymer microparticles with a particle size of 0.1 to 2.0 mm. Then, MOFs material and millimeter-sized polymer microparticles at a mass ratio of 1:2 to 10 were added to a coffee roaster. The operating temperature was 100 to 250℃, the stirring speed was 20 to 100 rpm, and the stirring time was 1 to 10 minutes. Subsequently, the particles were rapidly cooled using a cooling molding agent, and the unloaded MOFs material remaining on the surface was washed away, finally obtaining a MOFs-loaded polymer nanostructure composite material.

[0092] The melt blending described in this invention is equivalent to surface hot melting treatment, where melt blending simply melts the surface of the polymer particles.

[0093] Preferably, the MOF materials are selected from ZIF-8 (also known as MAF-4), ZIF-67, ZIF-L, ZIF-9, ZIF-90, PCN-222, PCN-224, IRMOF-3, IRMOF-8, IRMOF-9, HKUST-1 (also known as MOF-199 or CuBTC), Cu-TCPP, MOF-5 (also known as IRMOF-1), MOF-74, MOF-808, MOF-525, MIL-53 (Cr / Al / Fe), MIL-100 (Fe / Cr), MIL-101 (… One or more of the following MOF materials are selected: Fe / Cr), MIL-125(Ti), MIL-88A(Fe), MIL-88B(Fe), MIL-68(Al / Fe), NH2-MIL-125(Ti), NH2-MIL-88B(Fe), NH2-MIL-53(Al), UiO-66(Zr), NH2-UiO-66(Zr), UiO-66(Zr)-(OH)2, UiO-66(Zr)-COOH, UiO-66(Zr)-SO3H, UiO-67(Zr), and UiO-68. All of the above MOF materials are publicly available in the prior art, and the corresponding references for their preparation methods are detailed in Table 1.

[0094] Table 1. Preparation methods of MOFs

[0095]

[0096]

[0097]

[0098] More preferably, the MIL-88A (Fe), ZIF-67 and UiO-66 (Zr) in the embodiments can be efficiently separated by the method described in the existing utility model (patent number: ZL 202320109802.0), which further reduces the preparation cost of MOFs.

[0099] Preferably, the polymer material is a plastic product containing a thermoplastic polymer material; the plastic product is an injection-molded product, a vacuum-formed product, and / or a blow-formed product.

[0100] Preferably, the polymer material is a plastic product containing thermoplastic polymer material, which is a waste thermoplastic polymer resin material derived from recyclable materials in household waste.

[0101] Preferably, the waste thermoplastic polymer resin material includes injection molded products, blow molded products, and / or sporting goods containing thermoplastic polymer materials.

[0102] Preferably, the injection-molded product includes one or more of the following: boxes, buckets, trays, and containers with storage functions; more preferably, the injection-molded product includes disposable plates and / or disposable lunch boxes.

[0103] Preferably, the blow-molded article includes sealed bottle-type articles for holding cleaning agents, beverages or personal care products; more preferably, the blow-molded article includes one or more of empty laundry detergent bottles, empty beverage bottles, empty disinfectant bottles and empty cosmetic bottles.

[0104] Preferably, the stationery and sports goods include stationery and / or sporting goods; more preferably, the stationery and sports goods include one or more of plastic rulers, correction tape cases, and ballpoint pen cases.

[0105] More preferably, the thermoplastic polymer is one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyethylene terephthalate, ethylene-vinyl acetate copolymer (wherein the preferred mass fraction of ethylene is 10% to 50%), ethylene-vinyl alcohol copolymer (wherein the preferred mass fraction of ethylene is 20% to 40%), and acrylonitrile-butadiene-styrene trimer (wherein the preferred mass fraction of acrylonitrile is 15% to 35%, the preferred mass fraction of butadiene is 5% to 30%, and the preferred mass fraction of styrene is 40% to 60%).

[0106] More preferably, the polymer material is a PE plastic product. The reasons are as follows: First, PE is one of the most widely used polymer base materials and accounts for a large proportion of waste plastics; second, PE has a relatively low melting point of 110°C, so there is no need for ultra-high temperature treatment during the loading of MOFs, reducing energy consumption in the preparation process.

[0107] More preferably, the MOF material is selected from MIL-88A(Fe), ZIF-67, or UiO-66(Zr). The reasons are as follows: First, MIL-88A(Fe), ZIF-67, and UiO-66(Zr) are heat-resistant and can be prepared in large quantities, which meets the large-scale catalyst dosage requirements in actual water treatment. Second, the precursors used in MIL-88A(Fe), ZIF-67, and UiO-66(Zr) are available in industrial-grade specifications and are inexpensive. In particular, the low cost of raw materials used in MIL-88A(Fe), ZIF-67, and UiO-66(Zr) can reduce the cost per unit mass of catalyst.

[0108] More preferably, PE nanostructured composites loaded with MIL-88A(Fe) are used in water pollution treatment. The reasons are as follows: First, the preparation cost of MIL-88A(Fe) is lower than that of ZIF-67 and UiO-66(Zr), and the preparation conditions are mild, requiring no toxic organic solvents and easy to mass-produce; second, MIL-88A(Fe) is a relatively environmentally friendly material; third, MIL-88A(Fe) has been proven to not only efficiently adsorb arsenate in water, but also degrade various organic pollutants through photocatalysis and activation of hydrogen peroxide and persulfate, making it a multifunctional material. Therefore, PE nanostructured composites loaded with MIL-88A(Fe) show the greatest potential for engineering applications.

[0109] More preferably, the grinding speed is 12,000 to 13,000 rpm and the grinding time is 5 to 7 seconds. Within this grinding speed and grinding time range, the waste plastic can be cut into millimeter-sized polymer particles with a particle size between 0.5 mm and 1.0 mm, and the polymer particles can form the most pits, have the highest roughness, and be easy to load with subsequent MOFs.

[0110] More preferably, the stirring speed is 60–80 rpm, the heating temperature is 150–230 °C, and the time is 2.5–3.5 min. The loading of MOFs on millimeter-scale polymer particles is maximized only within this range of stirring speed, heating temperature, and duration, which induces more hierarchical porous structures and avoids particle adhesion and agglomeration.

[0111] More preferably, the mass ratio of MOFs material to millimeter-sized polymer particles is 1:3 to 5. This ratio represents the maximum mass ratio at which the MOFs powder is just fully loaded onto the millimeter-sized polymer particles. Further increasing the amount of MOFs added will result in excess unloaded MOFs filter powder, reducing the utilization rate of the MOFs powder.

[0112] More preferably, the cooling agent is tap water. Tap water has low operating costs, a high specific heat capacity, and good heat absorption, which can quickly reduce the temperature of the material surface. At the same time, water is a green and environmentally friendly solvent and will not have adverse effects on the environment.

[0113] In this invention, the cooling molding agent has two functions: first, to cool the composite material; and second, to wash away the unloaded MOF powder on the surface of the particles.

[0114] Secondly, the present invention provides a polymer composite material supported on MOFs for the adsorption and removal of pollutants in water; preferably, its application in the adsorption and removal of arsenic pollutants in water.

[0115] And / or, the present invention provides an application of the MOF-loaded polymer composite material in the field of oxidative degradation of pollutants in water; preferably, the MOF-loaded polymer composite material is used in the field of oxidative degradation of organic pollutants in water; more preferably, the organic pollutant is an antibiotic; further preferably, the antibiotic is a tetracycline antibiotic; even more preferably, the oxidative degradation of antibiotic pollutants in water includes one or more combinations of: water pollutants degraded based on activated hydrogen peroxide, water pollutants degraded based on activated persulfate, and water pollutants degraded based on activated ozone.

[0116] This invention provides an application of the aforementioned MOF-loaded polymer composite material in the preparation of flame-retardant products.

[0117] Thirdly, the present invention provides a continuous operation device for removing pollutants from water, the device comprising: a liquid inlet system, a reaction system, and a liquid discharge system; the liquid inlet system is used to introduce wastewater to be treated into the reaction system; the reaction system is loaded with a polymer composite material loaded with MOFs for removing pollutants from the wastewater to be treated; the liquid discharge system is used to discharge the treated water from the reaction system.

[0118] Preferably, the liquid inlet system includes a storage tank 1 for storing the wastewater to be treated; and is connected to the reaction system via a pipeline 3, on which a centrifugal pump 2, a first flow control valve 4, a first flow meter 5, and a pressure gauge 6 are sequentially installed. More preferably, the storage tank 1 is made of polytetrafluoroethylene (PTFE); and / or, more preferably, the pipeline 3 is made of PTFE.

[0119] Preferably, the liquid inlet system further includes an oxidant storage tank 7 for introducing the oxidant into the reaction system, which is connected to the reaction vessel 14 via a second pipeline 10; a peristaltic pump 8, a second flow control valve 9, and a second flow meter 11 are sequentially provided on the second pipeline 10.

[0120] More preferably, the oxidant storage tank 7 is used to store an aqueous solution of hydrogen peroxide, an aqueous solution of potassium persulfate, or an aqueous solution of sodium persulfate. More preferably, the mass concentration of the aqueous solution of hydrogen peroxide is 30%; the molar concentration of the aqueous solution of potassium persulfate is 150-300 mM; and the preferred molar concentration of the aqueous solution of sodium persulfate is 200-250 mM. More preferably, the pipe 10 is made of polytetrafluoroethylene.

[0121] Preferably, the reaction system includes a reaction vessel 14, with an aeration disc 12 at the bottom, and a first flange 13 and a second flange 15 at the top and bottom of the reaction vessel, respectively, for sealing the reaction vessel. The first flange 13 is located below the aeration disc 12. The first flange 13 and the second flange 15 are each provided with a barrier mesh with a pore size of 30 mesh, for preventing the loss of the polymer composite material loaded with MOFs. More preferably, the reaction vessel 14 is made of polytetrafluoroethylene (PTFE). More preferably, the loading mass of the polymer nanostructure composite material loaded with MOFs is 400 kg.

[0122] Preferably, the continuous operation device further includes an ozone generator 16 for supplying ozone to the reaction vessel 14, which is connected to the bottom of the reactor 14 via a pipe 19; a third flow control valve 17 and a third flow meter 18 are sequentially provided on the pipe 19.

[0123] More preferably, the pipe 319 is made of polytetrafluoroethylene.

[0124] Preferably, the liquid discharge system includes an outlet water collection tank 23, which is connected to the top of the reaction vessel 14 via a pipe 20; a fourth flow control valve 21 and a fourth flow meter 22 are sequentially installed on the pipe 20.

[0125] More preferably, the pipe 20 is made of polytetrafluoroethylene.

[0126] Fourthly, the present invention provides a method for removing contaminants from water using a continuously operating device, wherein the method is selected from any one of the following two methods:

[0127] Method 1: Removal of pollutants from water by adsorption; the method includes the following steps: loading the polymer nanostructure composite material loaded with MOFs into the reaction system, and then continuously pumping the wastewater to be treated into the reaction system through centrifugal pump 2 and first flow control valve 4 in the liquid inlet system. The water treated by the reaction system is continuously discharged into the liquid discharge system.

[0128] Method 2: Remove pollutants from water using advanced oxidation; the method further includes: loading the polymer nanostructured composite material loaded with MOFs into the reaction system, then introducing the wastewater to be treated into the reaction system via the liquid inlet system, while simultaneously introducing an aqueous solution of oxidant into the reaction system through a peristaltic pump 8 and a second flow control valve 9, and the water treated by the reaction system is continuously discharged into the liquid discharge system.

[0129] Unless otherwise stated, all reagents / instruments used in the embodiments and comparative examples of this invention are conventional commercially available reagents / instruments. Information on the experimental materials and instruments used in this invention is shown in Table 2:

[0130] Table 2 Sources of Raw Materials and Equipment Used

[0131]

[0132]

[0133] The following specific embodiments further illustrate the MOFs-waste plastic nanostructured composite material, its preparation method, and its application.

[0134] Example 1: Preparation of MIL-88A (Fe), ZIF-67 and UiO-66 (Zr) powders

[0135] MIL-88A(Fe) was prepared using 95% ethanol as solvent and ferric chloride and fumaric acid as precursors. Then, it was efficiently separated and dried using the continuous separation and purification apparatus for MOFs described in the utility model patent application (patent application number: 202320109802.0) to obtain a brownish-red MIL-88A(Fe) powder (refer to the preparation method in section 2.2 of the journal article: Mater. Res. Bull., 2020, 125, 110806). Figure 1 As shown in (a).

[0136] ZIF-67 was prepared using methanol as a solvent and cobalt nitrate hexahydrate and 2-methylimidazole as precursors. Then, it was efficiently separated and dried using the continuous separation and purification device for MOFs described in the utility model patent application (patent application number: 202320109802.0) to obtain purple ZIF-67 powder (see the preparation method in section S2 of the supporting information in the journal article: Environ. Sci. Technol., 2020, 54(16), 10289-10300). Figure 1 As shown in (b);

[0137] Using DMF as a solvent and zirconium tetrachloride and terephthalic acid as precursors, UiO-66(Zr) was prepared. Then, it was efficiently separated and dried using the method described in the existing utility model patent (patent application number: 202320109802.0) to obtain white UiO-66(Zr) powder (refer to the preparation method in section 2.1 of the journal article: Chem. Eng. J., 2019, 375, 121944). Figure 1 As shown in (c).

[0138] The prepared MOF powders were characterized by X-ray diffraction analysis and scanning electron microscopy. The test results are as follows:

[0139] Scanning electron microscopy image analysis as follows Figure 2 As shown, the prepared MIL-88A(Fe) particles exhibit a uniform spindle-shaped morphology, consistent with the morphology of MIL-88A(Fe) particles in the relevant reference (Environ. Sci. Technol., 2020, 54(16), 10289-10300); the prepared ZIF-67 particles exhibit a uniform dodecahedral morphology, consistent with the morphology of ZIF-67 in the relevant reference (Environ. Sci. Technol., 2020, 54(16), 10289-10300); and the prepared UiO-66(Zr) particles exhibit a uniform octahedral morphology, consistent with the morphology of UiO-66(Zr) in the relevant reference (Chem. Eng. J., 2019, 375, 121944).

[0140] Powder X-ray diffraction (PXRD) analysis results are as follows: Figure 3As shown, the diffraction peak pattern of MIL-88A(Fe) is the same as the simulation pattern in the relevant reference (Environ. Sci. Technol., 2020, 54(16), 10289-10300). The diffraction peak pattern of ZIF-67 is the same as the simulation pattern in the relevant reference (Environ. Sci. Technol., 2020, 54(16), 10289-10300). The diffraction peak pattern of UiO-66(Zr) is the same as the PXRD simulation pattern in the relevant reference (Chem. Eng. J., 2019, 375, 121944).

[0141] Example 2: Preparation of millimeter-sized PE microparticles

[0142] Waste plastics collected from the Beijing Asuwei Waste Comprehensive Treatment Center were sorted, and injection-molded products made of PE material (including empty disposable plates and empty disposable lunch boxes), blow-molded products (including empty laundry detergent bottles, empty beverage bottles, empty disinfectant bottles and empty cosmetic bottles) and stationery products (plastic rulers, correction tape casings and ballpoint pen casings) were selected. They were then crushed into small pieces no larger than 30mm using a hammer and scissors.

[0143] Weigh approximately 100g of waste plastic pieces made of the aforementioned PE material and place them in a cryogenic crusher. Set the freezing temperature to -70℃, the grinding speed to 12000rpm, and the freezing / grinding time to 5s. After processing, pour the internal mixture through a 16-mesh sieve and shake it, retaining the filtered particles. Then, pour the retained particles through a 32-mesh sieve and shake it, retaining the particles on the sieve. These particles are the millimeter-sized PE microparticles obtained. Name these millimeter-sized PE microparticles mmPE. A picture of the actual product is shown below. Figure 4 As shown, the particle size of the millimeter-sized PE microparticles obtained is between 0.5 and 1.0 mm.

[0144] The prepared mmPE was characterized using scanning electron microscopy (SEM), and the test results are as follows: SEM image analysis is shown below. Figure 5 As shown, the surface of the prepared mmPE microparticles is relatively rough and has pits, indicating that by controlling the parameters of the cryogenic crusher, a rough structure can be induced on the surface of the PE material.

[0145] Example 3: Preparation of PE nanostructured composite material loaded with MIL-88A(Fe)

[0146] 125g of MIL-88A(Fe) powder and 375g of mmPE microparticles were poured into a coffee roaster. The heating temperature was set to 230℃, and the stirring speed was set to 60 rpm. After stirring for 3 minutes, the mixture was immediately poured into a 32-mesh sieve while still hot and shaken to filter out the unloaded MIL-88A(Fe) powder, yielding approximately 475g of MIL-88A(Fe)-loaded PE nanostructured composite material. The particles remaining on the sieve were then repeatedly rinsed with 10kg of tap water (used as both a washing solution and a cooling agent) for 7 minutes. Finally, the surface moisture of the particles was dried in an oven. This material was named MmmPE, and a sample image is shown below. Figure 6 As shown in (a), the original mmPE surface changed from white to the brownish-red color of MIL-88A(Fe). By weighing the filtered powder without MIL-88A(Fe) loading, the loading rate of MIL-88A(Fe) on the mmPE was estimated to be close to 80%.

[0147] The prepared MmmPE surface was characterized by scanning electron microscopy, surface infrared spectroscopy, and X-ray photoelectron spectroscopy. The test results are as follows:

[0148] Scanning electron microscopy image analysis as follows Figure 7 As shown in (a), it can be observed that the surface roughness of MmmPE particles after melt blending is significantly improved, and a large number of spindle-shaped MIL-88A(Fe) particles are uniformly attached, indicating that this treatment method can successfully induce the formation of a composite material with a hierarchical porous structure.

[0149] Example 4: Preparation of PE milli-nano-structured composite materials loaded with ZIF-67

[0150] 125g of ZIF-67 powder and 375g of mmPE microparticles were poured into a coffee roaster. The heating temperature was set to 230℃, and the stirring speed was set to 60 rpm. After stirring for 3 minutes, the hot mixture was immediately poured into a 32-mesh sieve and shaken to filter out the unloaded ZIF-67 powder, yielding approximately 462.5g of ZIF-67-loaded PE nanostructured composite material. The particles remaining on the sieve were then repeatedly rinsed with 10kg of tap water for 7 minutes. Finally, the surface moisture of the particles was dried in an oven. This material was named ZmmPE, and a sample image is shown below. Figure 6 As shown in (b), the original mmPE surface changed from white to purple due to ZIF-67. By weighing the filtered unloaded ZIF-67 powder, the loading rate of ZIF-67 on the mmPE was estimated to be close to 70%.

[0151] The prepared ZmmPE surface was characterized using scanning electron microscopy (SEM), and the test results are as follows: SEM image analysis is shown below. Figure 7As shown in (b), it can be observed that the surface roughness of ZmmPE particles after melt blending is significantly improved, and a large number of ZIF-67 particles with a regular dodecahedral morphology are uniformly attached, indicating that this treatment method can successfully induce the formation of a composite material with a hierarchical porous structure.

[0152] Example 5: Preparation of PE nanostructured composite material loaded with UiO-66(Zr)

[0153] 125g of UiO-66(Zr) powder and 375g of mmPE microparticles were poured into a coffee roaster. The heating temperature was set to 230℃, and the stirring speed was set to 60 rpm. After stirring for 3 minutes, the mixture was immediately poured into a 32-mesh sieve while still hot and shaken to filter out the unloaded UiO-66(Zr) powder, yielding approximately 487.5g of UiO-66(Zr)-loaded PE nanostructured composite material. The particles remaining on the sieve were then repeatedly rinsed with 10kg of tap water for 7 minutes. Finally, the surface moisture of the particles was dried in an oven. This material was named UmmPE, and a sample image is shown below. Figure 6 As shown in (c), the original mmPE surface remained white without significant change. By weighing the filtered unloaded UiO-66(Zr) powder, the loading rate of UiO-66(Zr) on the mmPE was estimated to be close to 90%.

[0154] The prepared UmmPE surface was characterized using scanning electron microscopy (SEM), and the test results are as follows: SEM image analysis is shown below. Figure 7 As shown in (c), it can be observed that the surface roughness of UmmPE particles after melt blending is significantly improved, and a large number of UiO-66(Zr) particles with regular octahedral morphology are uniformly attached, indicating that this treatment method can successfully induce the formation of a composite material with a hierarchical porous structure.

[0155] Example 6: Physical property characterization of PE millinostructured composites loaded with MIL-88A (Fe), ZIF-67, and UiO-66 (Zr)

[0156] To investigate the structural characteristics of PE nanostructured composites loaded with MOFs, the particles prepared in Examples 2-5 were tested using a fully automated specific surface area and pore size analyzer, and the results are shown in Table 3. When the mmPE surface was not loaded with MOFs, the specific surface area and total pore volume were relatively low; when MOFs were attached to the mmPE surface interface, the specific surface area and total pore volume of the samples were significantly increased, indicating that the microporous and mesoporous structures of the MOFs themselves further improved the specific surface area and porosity of the mmPE, which has macropores, forming a hierarchical porous material.

[0157] Table 3. Specific surface area and pore characteristics of the particles prepared in Examples 2-5

[0158] Sample Name <![CDATA[Specific surface area (m 2 ·g -1 )]]> <![CDATA[Total pore volume (cm 3 ·g -1 )]]> mmPE 80.65 0.092 MmmPE 484.43 0.251 ZmmPE 501.36 0.354 UmmPE 783.19 0.447

[0159] Application Example 1

[0160] Arsenic contamination in drinking water has drawn global attention. Inorganic arsenic ions dominate groundwater, and under the same conditions, they are more toxic than organic arsenic ions. Arsenic from minerals can enter groundwater through hydrogeochemical and biogeochemical processes, leading to the presence of naturally occurring high-arsenic groundwater in some areas. Therefore, developing technologies for treating high-arsenic groundwater is of great significance to the health of local residents.

[0161] A continuously operating unit loaded with MmmPE adsorbents removes As(III) and As(V) from contaminated simulated groundwater. The continuously operating unit used is as follows: Figure 8 As shown. The reagents in the continuous operation device include disodium hydrogen arsenate heptahydrate (As(V)) and sodium arsenite (As(III)). The polymer nanostructured composite material with MOFs loaded in the continuous device is MmmPE prepared in Example 3. Figure 9 The diagram shown is a schematic of a continuous operation device (including equipment dimensions). 2, 4, 0.2, and 3 represent the diameter of the storage tank 1 and the water collection tank 23, the height of the storage tank 1 and the water collection tank 23, the diameter of the reaction vessel 14, and the effective height of the packing material in the reaction vessel 14, respectively. All lengths are in meters.

[0162] Use deionized water to prepare a solution with a concentration of 0.1 mg / L. -1 As(III) with 0.7 mg L -1 A mixed As(V) solution was used as a simulated groundwater solution contaminated with arsenic. At least 5 mL of sample was taken from the solution, filtered through a 0.22 μm polyethersulfone microporous membrane, and then the initial total arsenic concentration C of the solution was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). 0,As Close the first flow control valve 4 to disconnect the storage tank 1, which stores the wastewater to be treated, from the reaction vessel 14. Then, add the simulated groundwater solution to the storage tank 1, and add 400 kg of MmmPE to the reaction vessel 14. Turn on the centrifugal pump 2, the first flow control valve 4, and the fourth flow control valve 21, and adjust the pump speed of the centrifugal pump 2 to 500 mL / min. -1 Timing begins when liquid starts flowing from pipe 420. Every day thereafter, samples are taken from the outlet of pipe 420 (sample volume no less than 5 mL), filtered through a 0.22 μm polyethersulfone microporous membrane, and the residual total arsenic concentration and the Fe ion concentration dissolved from MmmPE in the solution are determined using inductively coupled plasma atomic emission spectrometry (ICP-AES), denoted as C0. t,As and C t,FeWhere t is the device running time corresponding to the sample taken from the start of timing. Plot C over 15 days. t,As / C 0,As and C t,Fe A curve that changes over time. According to C... t,As / C 0,As The time-varying curves were used to evaluate the removal of total arsenic from simulated groundwater by the continuously operating unit; based on C... t,Fe The time-varying curves were used to evaluate the Fe ion dissolution of MmmPE at different times in a continuously operating unit, and then to analyze the stability of MmmPE.

[0163] To eliminate the contribution of the substrate to total arsenic removal, MmmPE was replaced with the same mass of mmPE particles and added to reaction vessel 14. Other conditions remained unchanged, and the above steps were repeated. C1 was plotted over 15 days. t,As / C 0,As A curve that changes over time.

[0164] Depend on Figure 12 As shown, during a continuous 15-day operation period, MmmPE can achieve an adsorption and removal efficiency of over 99% for total arsenic, reducing the total arsenic concentration to the WHO-specified limit for drinking water arsenic (10 μg / L). -1 The following is a description of the continuous operation unit, which is capable of processing a cumulative total of 10,800 L of solution containing 0.8 mg·L⁻¹. -1 Simulated groundwater with total arsenic. The contribution of pure mmPE to total arsenic removal was not significant. During the treatment process, the concentration of Fe ions dissolved by MmmPE was low, consistently below 1 mg / L for 15 days. -1 This demonstrates the good stability and durability of MmmPE.

[0165] Application Example 2

[0166] TTC, OTC, and CTC are the three most widely used tetracycline antibiotics worldwide. They are used not only to treat bacterial infections in humans and animals but are also commonly used as feed additives. However, due to their poor degradation in humans and animals, a large portion of the parent compounds (up to 75%) are released into the aquatic environment through excrement, posing a serious threat to ecosystem balance and human health, especially the emergence of antibiotic resistance genes and "superbugs." Therefore, finding suitable water treatment processes to efficiently remove these tetracycline antibiotics is urgently needed.

[0167] The continuously operating unit is loaded with MmmPE-activated hydrogen peroxide coupled with ozone to degrade a mixture of TTC, OTC, and CTC in the water. The continuously operating unit used is as follows: Figure 10As shown. The reagents in the continuous operation device include H2O2, TTC, OTC, and CTC. The polymer nanostructured composite material with MOFs loaded in the continuous device is the MmmPE prepared in Example 3. Figure 11 The diagram shown is a schematic of a continuous operation device (including equipment dimensions). 2, 4, 1.2, 0.2, and 3 represent the diameters of the liquid storage tank 1 and the effluent collection tank 23, respectively. They also represent the height of the oxidant storage tank 7, the heights of the liquid storage tank 1 and the effluent collection tank 23, the diameter of the oxidant storage tank 7, the diameter of the reaction vessel 14, and the effective height of the packing material in the reaction vessel 14. All lengths are in meters.

[0168] Prepare a solution with a concentration of 10 mg / L using deionized water. -1 A mixed solution of TTC, OTC, and CTC was prepared, and at least 1 mL of the sample was taken and filtered through a 0.22 μm polyethersulfone microporous membrane. The initial concentrations (C0, C1) of TTC, OTC, and CTC in the solution were then determined using liquid chromatography. 0,TTC C 0,OTC and C 0,CTC Close the first flow control valve 4 to disconnect the reaction vessel 14 from the storage tank 1, close the second flow control valve 9 to disconnect the oxidant storage tank 7 from the reaction vessel 14, and close the third flow control valve 17 to disconnect the ozone generator 16 from the reaction vessel 14. Then, add the mixed solution to the storage tank 1 used to store the wastewater to be treated, and add 400g of MmmPE to the reaction vessel 14. Turn on the centrifugal pump 2, the first flow control valve 4, and the fourth flow control valve 21, and adjust the pump speed of the centrifugal pump 2 to 500mL / min. -1 The oxidant storage tank 7 contains hydrogen peroxide with a mass concentration of 30%. The peristaltic pump 8 and the second flow control valve 9 are turned on, and the pump speed of the peristaltic pump 8 is adjusted to 13 mL / h. -1 Turn on ozone generator 16 and the third flow control valve 17, and adjust the airflow of ozone generator 16 to 20g / h. -1 Timing begins when liquid starts flowing from pipe 4.20. Every day thereafter, a sample (at least 15 mL) is taken from the outlet of pipe 4.20, filtered through a 0.22 μm polyethersulfone microporous membrane, and the residual concentrations of TTC, OTC, and CTC in the sample are determined using liquid chromatography and denoted as C0. t,TTC C t,OTC and C t,CTC Simultaneously, the concentration of Fe ions dissolved from MmmPE in the solution was determined using inductively coupled plasma atomic emission spectrometry and denoted as C. t,Fe Simultaneously, the residual concentration of total organic carbon (TOC) in the solution was determined using a total organic carbon analyzer and denoted as C. t,TOCWhere t is the device running time corresponding to the sample taken from the start of timing. Plot C over 15 days. t,TTC / C 0,TTC C t,OTC / C 0,OTC C t,CTC / C 0,CTC C t,Fe and C t,TOC / C 0,TOC A curve that changes over time. According to C... t,TTC / C 0,TTC C t,OTC / C 0,OTC and C t,CTC / C 0,CTC The time-varying curves were used to evaluate the long-term degradation performance of the continuously operating unit against TTC, OTC, and CTC, as well as the catalyst durability; based on C t,Fe The time-varying curves were used to evaluate the Fe ion dissolution of MmmPE at different times in a continuously operating unit, thereby analyzing the stability of MmmPE; based on C t,TOC / C 0,TOC The time-varying curves were used to evaluate the removal rate of TOC from a mixed solution of TTC, OTC, and CTC by the continuously operating unit.

[0169] To eliminate the contribution of the substrate to the degradation of TTC, OTC, and CTC contaminants, MmmPE was replaced with the same mass of mmPE particles and added to reaction vessel 14. The above steps were repeated under the same conditions, and CT was plotted over 15 days. t,TTC / C 0,TTC C t,OTC / C 0,OTC C t,CTC / C 0,CTC C t,Fe and C t,TOC / C 0,TOC A curve that changes over time.

[0170] Depend on Figure 13 As shown, during a continuous 15-day operation period, MmmPE can achieve a degradation efficiency of over 90% for TTC, OTC, and CTC, and a TOC removal efficiency of over 60%. The device can cumulatively process 10,800 L of a solution containing 10 mg / L of TTC. -1 Wastewater containing TTC, OTC, and CTC was treated. Pure mmPE did not significantly contribute to the degradation of TTC, OTC, and CTC. During treatment, the concentration of Fe ions dissolved from mmPE was low, consistently below 1 mg / L for 15 days. -1 This demonstrates the good stability and durability of MmmPE.

[0171] Application Example 3

[0172] To explore the application potential of MOF-loaded polymer composites in the preparation of flame-retardant products, the thermal stability of the MOF-loaded polymer composites was tested using a thermogravimetric analyzer.

[0173] Figure 14 This section compares the thermogravimetric curves of the PE nanostructured composite material loaded with MIL-88A (Fe), ZIF-67, and UiO-66 (Zr) in this invention under air atmosphere. Figure 14 It was found that pure mmPE was almost completely thermally decomposed at 500℃ without MOF loading. However, when loaded with MIL-88A (Fe), ZIF-67, and UiO-66 (Zr), the resulting polymer composite still showed solid residues in the 500–800℃ range, indicating the formation of carbonaceous materials. Carbonaceous materials generally begin to burn in air above 800℃, while the ignition point of mmPE is between 340 and 500℃. Therefore, the residual carbonaceous materials adhering to the mmPE surface can significantly increase the ignition point of the original mmPE. Furthermore, the carbonaceous materials can act as a barrier, reducing the oxygen concentration around the mmPE surface microenvironment, thereby inhibiting the combustion of mmPE. To further confirm these conclusions, the thermal stability and minimum oxygen concentration required for combustion of the MOF-loaded polymer composite were tested using a limiting oxygen index analyzer. Figure 15 This paper compares the limiting oxygen index (LOI) during the combustion process of PE milli-nanostructured composite materials loaded with MIL-88A (Fe), ZIF-67, and UiO-66 (Zr) in this invention. When loaded with MIL-88A (Fe), ZIF-67, and UiO-66 (Zr), the LIOIs of the resulting polymer composites are 32%, 29%, and 36%, respectively, while the LIOI of pure mmPE is 16%. It is evident that the LIOIs of the polymer-loaded composites are significantly higher than those of pure mmPE, exceeding 27% (materials with an LIOI higher than 27% are generally considered non-flammable). This indicates that the carbonaceous microdomains formed under high-temperature conditions after the introduction of MOFs can control the oxygen content in the microenvironment at the mmPE interface, thereby preventing material combustion.

[0174] Application Example 4

[0175] To further investigate the influence of various factors and parameters in the preparation process of MOF-loaded polymer composites on the properties and performance of MOF-loaded polymer composites, orthogonal experiments were conducted in this application example. MIL-88A(Fe) was selected as a representative MOF material. During the mechanical grinding and crushing process, freezing temperature, grinding time (i.e., freezing time), and grinding speed were selected as factors. During the melt blending process, stirring temperature, stirring time, stirring speed, and the mass ratio of the MOFs to the freeze-ground polymer material (referred to as the "stirring ratio") were selected as factors. For each of the above seven factors, two levels were selected, and the values ​​of the selected levels are shown in Table 4.

[0176] Table 4. Factors and corresponding levels selected in the orthogonal experiment.

[0177] factor Level 1 Level 2 Freezing temperature -60℃ -70℃ Grinding time 5s 7s Grinding speed 12000rpm 13000rpm Stirring temperature 150℃ 230℃ Stirring time 2.5min 3.5min Stirring speed 60rpm 80rpm mixing ratio 1:3 1:5

[0178] Based on the above factors and levels, L8(2) can be used. 7 The experiment was designed using an orthogonal array, and the different combinations of factors and their levels are shown in Table 5.

[0179] Table 5L8(2) 7 Orthogonal array

[0180]

[0181]

[0182] In this table, columns 1 to 7 represent seven factors: freezing temperature, grinding time (i.e., freezing time), grinding speed, stirring temperature, stirring time, stirring speed, and stirring ratio. The numbers 1 and 2 below the column numbers represent the selected level 1 and level 2 of the corresponding factors, respectively. The results are further summarized in Table 6.

[0183] Table 6 shows the combinations of experimental conditions obtained from the orthogonal array.

[0184]

[0185] For each group of experiments, the average particle size (hereinafter referred to as "average particle size") and the loading rate of MIL-88A(Fe) (hereinafter referred to as "loading rate") of the MOF-loaded polymer composite material were selected as indicators to measure the physicochemical properties of the MOF-loaded polymer composite material. The average particle size was directly measured by a laser particle size analyzer, and the loading rate was calculated during the execution of Example 3. After performing the operation of Application Example 1 on the MOF-loaded polymer composite material, the total arsenic removal rate (hereinafter referred to as "total arsenic removal rate") of the material after 15 hours of continuous device operation was selected as an indicator to measure the performance of the MOF-loaded polymer composite material. The experimental results are shown in Table 7.

[0186] Table 7 Results of the orthogonal experiment

[0187]

[0188]

[0189]

[0190]

[0191] Where K1 represents the sum of the indicators examined in the trials for the first level (column midpoint value 1) of factors A, B, C, D, E, F, and G. For example, for K1 in column 1, the average particle size with a column midpoint value of 1 is 1.0, 1.0, 0.8, and 0.8, which sums to 3.6. K2 represents the sum of the indicators examined in the trials for the second level (column midpoint value 2) of factors A, B, C, D, E, F, and G. For example, for K2 in column 1, the average particle size with a column midpoint value of 2 is 0.8, 0.8, 1.0, and 1.0, which sums to 3.6. k1 and k2 are the average values ​​of K1 and K2, respectively, which are the ratios of K1 and K2 to the frequency of occurrence of each level 1 and level 2 in each column. Since each level 1 and level 2 occurs 4 times, k1 and k2 should be divided by 4 to obtain the results in the table.

[0192] The larger the range, the greater the impact of changes in the level of this factor on the experimental indicators. From the above analysis, we can conclude that the factor corresponding to the column with the largest range is grinding speed, while the ranges of the other columns are all 0, indicating that changes in grinding speed have the greatest impact on average particle size, loading rate, and total arsenic removal rate.

[0193] While the specific embodiments of the present invention have been described above, they are not intended to limit the scope of protection of the present invention. Based on the technical solutions of the present invention, various modifications or variations that can be made by those skilled in the art without creative effort are still within the scope of protection of the present invention.

Claims

1. A method for preparing a polymer composite material loaded with MOFs, characterized in that: The method comprises the following steps: freezing and crushing the polymer material, then adding the MOFs material for melt blending, so that the MOFs material is loaded on the surface of the polymer material, cooling, and separating to obtain the polymer material loaded with MOFs.

2. The preparation method according to claim 1, wherein The polymer material is a material containing a thermoplastic polymer; Preferably, the polymer material is a plastic product containing a thermoplastic polymer; More preferably, the thermoplastic polymer includes one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyethylene terephthalate, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer and acrylonitrile-butadiene-styrene terpolymer; More preferably, the thermoplastic polymer includes one or more of polyethylene, polypropylene, polystyrene and polyethylene terephthalate.

3. The preparation method according to claim 1 or 2, wherein The MOFs material is a MOFs material with a thermal decomposition temperature higher than 120°C; Preferably, the MOFs material is selected from ZIF-8, ZIF-67, ZIF-L, ZIF-9, ZIF-90, PCN-222, PCN-224, IRMOF-3, IRMOF-8, IRMOF-9, HKUST-1, Cu-TCPP, MOF-5, MOF-74, MOF-808, MOF-525, MIL-53 (Cr / Al / Fe), MIL-100 (Fe / Cr), MIL-101 (Fe / Cr), MIL-125 (Ti ), one or more of MIL-88A(Fe), MIL-88B(Fe), MIL-68(Al / Fe), NH2-MIL-125(Ti), NH2-MIL-88B(Fe), NH2-MIL-53(Al), UiO-66(Zr), NH2-UiO-66(Zr), UiO-66(Zr)-(OH)2, UiO-66(Zr)-COOH, UiO-66(Zr)-SO3H, UiO-67(Zr) and UiO-68; More preferably, the MOFs material is selected from one or more of ZIF-8, ZIF-67, ZIF-L, ZIF-9, ZIF-90, MIL-53 (Cr / Al / Fe), MIL-100 (Fe / Cr), MIL-101 (Fe / Cr), MIL-125 (Ti), MIL-88A (Fe), MIL-88B (Fe), MIL-68 (Al / Fe), NH2-MIL-125 (Ti), NH2-MIL-88B (Fe), NH2-MIL-53 (Al) and UiO-66 (Zr).

4. The preparation method according to any one of claims 1 to 3, wherein The freezing conditions are: the freezing temperature is -20 to -80°C; Preferably, the freezing temperature is -60 to -70°C; And / or, the freezing time is 1 to 30 seconds; preferably, the freezing time is 5 to 7 seconds.

5. The preparation method according to any one of claims 1 to 4, wherein The crushing adopts mechanical grinding crushing; Preferably, the conditions for mechanical grinding and crushing are: the grinding speed is 10000-30000 rpm; preferably, the grinding speed is 12000-13000 rpm; And / or, the grinding time is 1 to 30 seconds; preferably, the grinding time is 5 to 7 seconds.

6. The preparation method according to any one of claims 1 to 5, wherein The particle size of the polymer material after freeze grinding ranges from 0.1 to 2.0 mm; Preferably, the particle size of the polymer material after crushing and grinding is in the range of 0.5 to 1.0 mm.

7. The preparation method according to any one of claims 1 to 6, wherein Adding MOFs material to the frozen ground polymer material, mixing, and melt blending; Preferably, the mass ratio of the MOFs to the polymer material after freeze-grinding is 1:2-10; more preferably, the mass ratio of the MOFs to the polymer material after freeze-grinding is 1:3-5; And / or, preferably, heating and stirring are used during hot melt treatment, and the conditions are: the heating temperature is 100-250°C; more preferably, the heating temperature is 150-230°C; and / or, the heating and stirring time is 1-10 min; more preferably, the heating and stirring time is 2-4 min; and / or, the stirring speed is 20-100 rpm; more preferably, the stirring speed is 60-80 rpm.

8. The preparation method according to any one of claims 1 to 7, wherein The cooling is performed by using a cooling molding agent for cooling; Preferably, the mass ratio of the cooling molding agent to the polymer composite material loaded with MOFs is 10 to 50:1; more preferably, the mass ratio of the cooling molding agent to the polymer composite material loaded with MOFs is 20 to 30:1; And / or, preferably, the cooling treatment time is 1 to 10 minutes; more preferably, the cooling treatment time is 4 to 7 minutes; And / or, preferably, the cooling molding agent is selected from one or more of water, ethanol and N,N-dimethylformamide; more preferably, the cooling molding agent is water.

9. A polymer composite material loaded with MOFs, characterized in that: The MOFs-loaded polymer composite material is prepared by the preparation method described in any one of claims 1-8.

10. Use of the polymer composite material loaded with MOFs according to claim 9 in the field of adsorption and removal of pollutants in water or oxidation and degradation of pollutants in water; Preferably, the polymer composite material loaded with MOFs is used in the field of adsorption and removal of arsenic pollutants in water; And / or, preferably, the application of the polymer composite material loaded with MOFs in the field of oxidative degradation of organic pollutants in water; more preferably, the organic pollutants are antibiotics; further preferably, the oxidative degradation of organic pollutants in water includes: One or a combination of two or more of the following: degradation of pollutants in water based on activated hydrogen peroxide, degradation of pollutants in water based on activated persulfate, and degradation of pollutants in water based on activated ozone.

11. Use of the MOFs-loaded polymer composite material according to claim 9 in preparing flame-retardant products.

12. A continuously operating device for removing pollutants from water as claimed in claim 10, characterized in that: The device comprises: a liquid inlet system, a reaction system and a liquid discharge system; The liquid inlet system is used to introduce the wastewater to be treated into the reaction system; The polymer composite material loaded with MOFs in the reaction system is used to remove pollutants in the wastewater to be treated; The liquid discharge system is used to discharge the treated water in the reaction system.

13. The continuously operating device according to claim 12, wherein: The liquid inlet system comprises a liquid storage tank (1) for storing wastewater to be treated, which is connected to the reaction system via a pipeline (3), wherein a centrifugal pump (2) is provided on the pipeline (3); and / or a first flow control valve (4) is provided on the pipeline (3); and / or a first flow meter (5) is provided on the pipeline (3); and / or a pressure gauge (6) is provided on the pipeline (3).

14. The continuously operating device according to claim 12 or 13, wherein: The liquid inlet system also includes an oxidant storage tank (7) for introducing the oxidant into the reaction system, which is connected to the reaction container (14) via a second pipeline (10); The second pipeline (10) is provided with a peristaltic pump (8); and / or, the second pipeline (10) is provided with a second flow control valve (9); and / or, the second pipeline (10) is provided with a second flow meter (11); Preferably, the oxidant storage tank (7) is used to store an aqueous hydrogen peroxide solution, an aqueous potassium persulfate solution or an aqueous sodium persulfate solution.

15. The continuously operating device according to any one of claims 12 to 14, wherein: The reaction system comprises a reaction container (14) for directly loading the polymer composite material loaded with MOFs, an aeration plate (12) is arranged at the bottom of the reaction container, and a first flange (13) and a second flange (15) are arranged at the top and bottom of the reaction container respectively for sealing the reaction container, and the first flange (13) is below the aeration plate (12); Preferably, a barrier net is provided in the first flange (13) and the second flange (15), respectively. The aperture of the barrier net is preferably 30-60 meshes, so as to prevent the loss of the polymer composite material loaded with MOFs while ensuring normal water flow.

16. The continuously operating device according to any one of claims 12 to 15, wherein: The continuous operation device also includes an ozone generator (16) for delivering ozone to the reaction vessel (14), which is connected to the bottom of the reactor (14) through a pipeline three (19); The pipeline three (19) is provided with a third flow control valve (17); and / or the pipeline three (19) is provided with a third flow meter (18).

17. The continuously operating device according to any one of claims 12 to 16, wherein: The liquid discharge system comprises a water collection tank (23), which is connected to the top of the reaction container (14) through a pipeline (20); The pipeline four (20) is provided with a fourth flow control valve (21); and / or the pipeline four (20) is provided with a fourth flow meter (22).

Citation Information

Patent Citations

  • Device for continuously separating and purifying MOFs

    CN220003969U